From gossip to conspiracy thinking: Analysis and scriptural evaluations - Arbuckle, Gerald A. (The Australasian Catholic record, 2022)
Gossip is designed to ruin an individual's or a group's reputation. Gossip demonises its victims in private. 'There is no such thing as innocent gossip', says Pope Francis. When gossip moves into the public forum, however, we have witch-hunting or scapegoating, reinforced by conspiracy theorising. The worlds flooded these days with conspiracy theories, the beliefs, contrary to reality, that individuals or groups are secretly acting to accomplish some malevolent purpose. Once COVID-19 was identified, conspiracy theories began to emerge and continue to do so. Some said it was a hoax or a campaign to disrupt the presidential re-election of Donald Trump; others the pharmaceutical industry deliberately spreads the disease.